2020
DOI: 10.47009/ajcpn.2020.8.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Association between Thyroid Profile and Serum Bilirubin Levels in Term Neonates on Day 3 of Life

Abstract: Background: Neonatal indirect hyperbilirubinemia is a common clinical scenario that manifests as jaundice in the first week of life. Studies have shown that the physiological peak of serum bilirubin (SBR) levels is highest at 72 hours of life as a result of which SBR is measured at  72 hours of life routinely. The American Academy of Pediatricians (AAP) recommends routine screening for congenital hypothyroidism within the first week of life for all neonates. In common practice, both parameters are assessed sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…~ 40 ~ Kadambi et al [11] in their study correlated thyroid Profile and serum bilirubin levels assessed in term neonates at 72 hours of life on 105 term neonates born through cesareansection. [12] found that newborns who developed significant hyperbilirubinemia male: female ratio was 1.07:1.…”
Section: Discussionmentioning
confidence: 99%
“…~ 40 ~ Kadambi et al [11] in their study correlated thyroid Profile and serum bilirubin levels assessed in term neonates at 72 hours of life on 105 term neonates born through cesareansection. [12] found that newborns who developed significant hyperbilirubinemia male: female ratio was 1.07:1.…”
Section: Discussionmentioning
confidence: 99%